PENGARUH PERSEPSI WISMAN MENGENAI MARKET POSITIONING, BRAND IMAGE DAN SOCIAL RESPONSIBILITY TERHADAP KINERJA STRATEGI BAURAN PEMASARAN BIRO PERJALANAN WISATA SERTA DAMPAKNYA PADA BISNIS PARIWISATA BERKELANJUTAN DI BALI - Wisnu Bawa Tarunajaya (JURNAL KEPARIWISATAAN, 2009)
The sustainable Balinese tourism development highly depends on the tourists' perception of the market positioning, brand image and the social responsibility of the tourism industry especially travel agencies. By utilizing methods of descriptive and explanatory surveys, this study finds out that the tourists' perception of the market positioning of tourism destination of Bali shows that the indicator of on the uniqueness of the Balinese culture is better than their expectation. Their perception of the brand image is found that the indicators of natural tourism object and places of interests are also better than their expectation. Meanwhile, their perception of the social responsibility of the travel agencies is considered to have a good influence on the indicator of their participation toward the improvement of the local welfare. The mixed marketing strategy certainly has a significant and positive influence toward the sustainable tourism development, but the government, commitment of the related industry, and the awareness and involvement of the local community also play important roles.